Phenotypic Florfenicol Resistance in floR ‐Harbouring Flavobacterium psychrophilum Isolates ( CC ‐ ST90 ): A Case Study From Danish Freshwater Rainbow Trout Aquaculture - Valentina L. Donati; Lone Madsen (Journal of Fish Diseases, 2026)
Monitoring antimicrobial resistance (AMR) in fish pathogens is essential for supporting sustainable aquaculture. In this study, susceptibility testing and genome sequencing were used to characterize the AMR profile of seven Flavobacterium psychrophilum originating from Danish rainbow trout farms (2019–2022). To establish epidemiological context and baseline virulence, isolates were also subjected to genome‐based Multi‐Locus Sequence Typing (MLST), serotyping and, for a subset, in vivo LD 50 testing. The analysis revealed changes in the susceptibility to antimicrobials used in Danish aquaculture. Most importantly, reduced susceptibility to florfenicol was observed in two isolates originating from a farm experiencing ineffective treatment (disc diffusion diameter of 7–8 mm, MIC > 16 μg mL −1 ). These isolates (serotype Th) belonged to a clonal complex previously unreported in the Nordic countries (CC‐ST90), and the genome analysis revealed a floR gene (413 aa) lying in a large genomic island, putatively conferring this property. The high diversity of the floR GC content (57.4%) from the floR ‐harbouring genomes (32.7%–32.8%) suggested its recent acquisition. Since florfenicol is the drug of choice for this infection in Denmark, these observations are highly relevant. However, in vitro lab and in vivo animal experiments are needed to confirm the activity of floR and support the clinical relevance of these findings. Also, a larger bacterial panel is needed to evaluate potential trends across farms/regions.